2016
DOI: 10.1021/acs.jpcc.6b02526
|View full text |Cite
|
Sign up to set email alerts
|

Size-Dependent Transformation of α-Fe into γ′-Fe4N in Nanocrystalline the Fe–NH3–H2 System

Abstract: On the basis of the results of experiments concerning nanocrystalline iron nitriding with ammonia−hydrogen mixtures, it was found that α-iron crystallites transform to iron nitride γ′-Fe 4 N in their whole volume in the order of their size, from the largest to the smallest ones. During the phase transition, the saturated solid solution of nitrogen in α-iron, being in the chemical equilibrium state, changes into an unsaturated solid solution of nitrogen in γ-iron, being in the transition state, and then to γ′-n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 47 publications
0
31
0
Order By: Relevance
“…In the state of chemical equilibrium, when the chemical potential of nitrogen is equal to the absolute value of the potential change in the deformed crystal lattice of nanocrystalline iron, the saturated solution of α-Fe(N)-which is in a state of chemical equilibrium-is transformed to an unsaturated solution of nitrogen in the γ-iron crystallographic phase-which, in turn, is in a state of transition-and further to γ'-Fe 4 N nitride, which is again in the chemical equilibrium state [18,19]. The step change in the nanocrystalline iron nitriding rate (Figures 2 and 3) can be explained by the gradual change in the degree of coverage of the iron surface with nitrogen (Figure 4), caused by the gradual change in the free enthalpy of nitrogen segregation (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the state of chemical equilibrium, when the chemical potential of nitrogen is equal to the absolute value of the potential change in the deformed crystal lattice of nanocrystalline iron, the saturated solution of α-Fe(N)-which is in a state of chemical equilibrium-is transformed to an unsaturated solution of nitrogen in the γ-iron crystallographic phase-which, in turn, is in a state of transition-and further to γ'-Fe 4 N nitride, which is again in the chemical equilibrium state [18,19]. The step change in the nanocrystalline iron nitriding rate (Figures 2 and 3) can be explained by the gradual change in the degree of coverage of the iron surface with nitrogen (Figure 4), caused by the gradual change in the free enthalpy of nitrogen segregation (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…A hysteresis was observed for the dependence of the nitriding degree on nitriding potential [13][14][15][16][17]. It was also found that the chemical potentials of nitrogen occurring in all three parts of the system-in the gaseous phase, on the iron nanocrystallite surface and in nanocrystallite volume -equaled one another in the stationary states, i.e., chemical equilibrium was established [16,18,19]. There was only a reaction of catalytic ammonia decomposition [20].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the results of gravimetric investigations of the nanocrystalline iron nitriding processes in atmospheres containing ammonia and hydrogen, it can be concluded that nanomaterials do not react chaotically but in a precisely defined order of increasing energy of transformation in the thermodynamic region of reaction, or of decreasing surface to volume ratio (geometrical aspect) in the kinetic region [31]. Based on these statements, a number of methods were developed to determine nanocrystallite size distribution, and it was stated that in the nanocrystalline iron doped with hardly reducible metals oxides the distribution was bimodal [32,33].…”
Section: Introductionmentioning
confidence: 99%